THE EFFECT OF SOURCE OF STRESS AND COPING STRATEGY ON STRESS SYMPTOMS OF THE CUSTOMER’S FAMILY OF ILLEGAL LOANS - Lenny Alfidayanti; Euis Sunarti (Journal of Child, Family, and Consumer Studies, 2023)
Human needs are so complex that it causes a mismatch between expenses and income generated. Debt is an alternative that is chosen so that family needs are still met, even though being in debt is prone to stress risks. This study aims to analyze the relationship between sources of stress, coping strategies, and stress symptoms, as well as the influence of sources of stress and coping strategies on the stress symptoms of illegal loans customers' families. The subjects in this study were active illegal loans customers in Purwasari Village. The sampling technique used simple random sampling method, which included quantitative research, with a sample size of 60 people. Data and information were collected through direct interviews using a questionnaire. Data were processed using descriptive, correlation, and multiple linear regression tests. The results showed that almost all sources of stress were in the low category, all coping strategies were in the low category, and more than half of the stress symptoms were in the low category. There is a significant positive relationship between the number of children and sources of stress, sources of stress are also significantly positively related to coping strategies and stress symptoms. There is a positive influence on the number of banks and sources of stress on the stress symptoms of illegal loans customers.